10 entry points for environmental peacebuilding in Mindanao, Phillippines. - Medina, Leonardo; Vaselli, Alessandra; Savelli, Adam; Torres, Mark Anthony (2024)
Environmental peacebuilding entails a broad range of theories and practices around the management of environmental issues that integrate goals to build more just and peaceful societies. Tailoring the management of natural resources and the cultivation of resilience towards supporting sustainable peacebuilding and peacekeeping goals prove relevant throughout conflict-affected Muslim Mindanao. The main challenge lies in identifying suitable mechanisms for environmental peacebuilding and integrating them in a cohesive manner. This involves adopting an approach where various policies and programs synergistically contribute to overarching strategies, avoiding the pitfalls of siloed approaches. By doing so, policymakers can harness the potential of environmental peacebuilding to foster sustainable development, resilience, and lasting peace in Mindanao. This report combines perceptions from a stakeholder consultation workshop and a literature review to propose ten entry points for environmental peacebuilding in Mindanao, exploring a diversity of strategies for environmental resource management and climate adaptation to support ongoing peacekeeping and peacebuilding efforts in the region.